The Effect of Inflation, Islamic Bank Financing, and Unemployment on Economic Growth - Putri Anggraini; Nurul Jannah; Imsar (Islamic Economics and finance in Focus, 2026)
Economic growth is a key indicator of regional economic performance, yet it remains vulnerable to macroeconomic fluctuations caused by inflation, financial intermediation, and labor market conditions. This study aims to analyze the short-run and long-run effects of inflation, Islamic bank financing, and the unemployment rate on economic growth in Medan City. A quantitative research approach was employed using the Vector Error Correction Model (VECM) with 40 quarterly secondary data observations covering the period from 2016 to 2025. The Granger causality test identified a unidirectional relationship from economic growth to the unemployment rate and from inflation to Islamic bank financing. The long-run VECM estimation revealed that inflation has a significant negative effect on economic growth, whereas in the short run it exerts a significant positive effect due to moderate demand-pull inflation. Islamic bank financing and the unemployment rate showed no significant partial effects in either the short run or the long run. The Impulse Response Function indicated that inflation shocks initially generated negative responses before converging toward equilibrium, while unemployment shocks produced gradually diminishing positive responses. Variance Decomposition confirmed that economic growth is primarily explained by its own innovations, with unemployment contributing the largest external shock. These findings imply that maintaining price stability and strengthening the informal labor sector are essential for enhancing the long-term macroeconomic resilience of Medan City.